200x
4x3+10x2-6x 2x(2x2+5x-3) 2x(2x-1)(x+3)
12x2 - 28x - 15= 12x2 - 18x - 10x - 15= 6x(2x - 3) - 5(2x - 3)= (6x - 5)(2x - 3)
(2x-4)(x-1) = 0
8x3 + 4x2 + 6x + 3 = 4x2(2x + 1) + 3(2x + 1) = (2x + 1)(4x2 + 3)
The GCF is 2x.
8
200x
(6x^3-9x^2) / (2x-3) = 3x^2((2x-3) / (2x-3) = 3 x ^2 (3 x squared)
8x2 + 6x - 9 = 8x2 + 12x - 6x - 9 = 4x(2x + 3) - 3(2x + 3) = (2x + 3)(4x - 3)
6x^2, six x squared.
6X squared
4x3+10x2-6x 2x(2x2+5x-3) 2x(2x-1)(x+3)
Well, darling, the answer to 2X times 3X is 6X^2. Just multiply the coefficients and add the exponents because math doesn't have time for drama. So there you have it, simple and straight to the point.
Oh, dude, when you add 6x squared and 2x squared, you get 8x squared. It's like combining 6 apples with 2 apples and ending up with 8 apples. So, in math terms, 6x squared plus 2x squared equals 8x squared. Easy peasy!
12x2 - 28x - 15= 12x2 - 18x - 10x - 15= 6x(2x - 3) - 5(2x - 3)= (6x - 5)(2x - 3)
6x2 + 10x = 2x*(3x + 5)